Efeitos das barreiras não tarifárias nas exportações de manga in natura - Costa, Luana Gonçalves Euclydes Borges da (Universidade Federal de São Carlos, 2006)
The fruit sector is found in expansion, being considered one of the fastest emerging and potential in the Brazilian agribusiness. The fruit chain has been affected by the increase in global competitiveness, where the big producers and retailers, focusing on the strengthening of their competitive position have amplified their strategies and acquisitions leading to a greater market concentration, a greater asymmetry of power and more complex configuration of this chain worldwide. The mango is in the spotlight in the Brazilian fruit culture, it is the third best exported fruit (113 thousand tons) in 2005. Brazil was eighth in worldwide production of mango in 2005, producing 850.000 tons. The northeast was the main productive area, responsible for 66% of all national production. The fruit sector is strongly affected by non-tariff barriers (NTBs), especially technical and phytosanitary. The restrictions have represented serious obstacles to the Brazilian fruit culture expansion in the international market. Therefore, the general goal of this research was analyze the productive chain of the exported Brazilian mango, focusing on the imposition of non-tariff barriers in the production, harvest, post harvest and distribution of national producers of mango in natura, where the study of case was selected as a more adequate method for the research and thus as multicase study was carried through. Some results found stand out: the technical barriers (having a phytosanitary state) are more frequent in mango exportation; the fruit is sold indirectly; the agriculture practice and non-tariff barriers are interrelated and finally, the consume behavior in different markets and consumers interfere in the process and practices adopted by the producers.
Keywords: Canais de distribuição; Barreiras não-tarifárias; Manga; Non-tariff barriers; Marketing channels; Mango; ENGENHARIAS::ENGENHARIA DE PRODUCAO